Are patient outcomes improved by models of professionally-led community HIV management which aim to be person-centred? A systematic review of the evidence. Issue 9 (2nd September 2021) - Abboah-Offei, M.; Bristowe, K.; Harding, R.
ABSTRACT: UNAIDS advocates person-centred care (PCC) for people living with HIV/AIDS (PLWHA) to improve outcomes and wellbeing. We appraised the evidence of person-centred models of community HIV care delivered or led by trained healthcare professionals and its impact on care outcomes. A systematic review was conducted in line with PRISMA guidance. Six electronic databases (CINAHL, Embase, PubMed, Medline, PsycINFO and Web of Science) were searched from January 1980 to April 2019. We included primary studies of any design of PCC models; for adults aged ≥15 years; that were delivered or led by trained HCP. Data were extracted including study location, design, quality, outcomes measured and effectiveness. Five out of 1393 studies met the inclusion criteria, of which four were from a high-income country and one a lower-middle income country. Of the PCC components (physical, psychological, social and spiritual wellbeing) delivered alongside HIV clinical management, one study delivered 2, two studies delivered 3 and two studies delivered all 4 components. This review highlights the lack of outcome evidence for person-centred HIV care, and of concurrent focus on all domains of concern for PLWHA within interventions. Clear articulation of the meaning, practice of PCC and implementation strategies are needed to meet policy recommendations.